2018
DOI: 10.1007/s40263-018-0567-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glatiramer Acetate on B Cell-Mediated Pathogenesis of Multiple Sclerosis

Abstract: Growing evidence indicates that B cells play a key role in the pathogenesis of multiple sclerosis (MS). B cells occupy distinct central nervous system (CNS) compartments in MS, including the cerebrospinal fluid and white matter lesions. Also, it is now known that, in addition to entering the CNS, B cells can circulate into the periphery via a functional lymphatic system. Data suggest that the role of B cells in MS mainly involves their in situ activation in demyelinating lesions, leading to altered pro- and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 112 publications
0
16
1
Order By: Relevance
“…It has been reported that GLAT reduces the relative frequency of B cells, plasmablasts and memory B cells in the peripheral blood of MS patients [31,32]. We could only detect slight differences in relative B cell subset frequencies and GLAT seems to have a less profound effect on B cell subsets when compared to other DMDs.…”
Section: Plos Onecontrasting
confidence: 64%
“…It has been reported that GLAT reduces the relative frequency of B cells, plasmablasts and memory B cells in the peripheral blood of MS patients [31,32]. We could only detect slight differences in relative B cell subset frequencies and GLAT seems to have a less profound effect on B cell subsets when compared to other DMDs.…”
Section: Plos Onecontrasting
confidence: 64%
“…While some studies reported no relevant modulation by glatiramer acetate regarding the overall lymphocyte and B cell count [ 90 , 98 , 137 ], others described an absolute and relative decrease of B cells in patients treated with glatiramer acetate [ 138 , 139 ]. Despite these discrepancies, several studies agree that glatiramer acetate treatment increases the proportion of interleukin-10 producing regulatory B cells and reduces the amount of memory B cells and plasmablasts [ 138 , 140 , 141 ]. Only one study reports that B cells of glatiramer acetate-treated patients produced higher amounts of interleukin-6 the longer they had been treated [ 138 ].…”
Section: Effects Of Ms Medications On Peripheral B Cells In Humansmentioning
confidence: 99%
“…Only one study reports that B cells of glatiramer acetate-treated patients produced higher amounts of interleukin-6 the longer they had been treated [ 138 ]. Furthermore, total IgG and IgM levels were shown to be elevated upon glatiramer acetate treatment [ 138 ], probably due to the observation that the majority of treated patients generate non-neutralizing anti-glatiramer acetate IgG antibodies [ 140 ]. While one study observed similar blood BAFF levels in patients with or without glatiramer acetate, two other reports that MS patients treated with glatiramer acetate had significantly higher serum BAFF levels [ 52 , 98 , 142 ].…”
Section: Effects Of Ms Medications On Peripheral B Cells In Humansmentioning
confidence: 99%
“…It has also been shown that GA can influence the function of B cells which may modulate inflammation in CNS by producing antibodies, pro-inflammatory cytokines and presenting antigen to effector T cells [ 6 ]. Glatiramer acetate modulates B cells functions by converting memory B cells known to contribute to the T cell-dependent inflammatory response into B regulatory cells and reduce the production of the pro-inflammatory cytokines IL-6 and tumor necrosis alpha factor (TNF-α) by B cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%